2006
DOI: 10.1108/13598540610662112
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating collaborative joint efforts with suppliers: the effects of trust, transaction specific investment and information network in the Dutch flower industry

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:573577 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Different studies of alliances have demonstrated that trust and commitment are two clear antecedents of the generation of cooperative behaviours between partners. First, trust is a major facilitator of cooperation because partners will only take high risks in cooperation when they have confidence in their counterparts (Morgan & Hunt, 1994;Lancastre & Lages, 2006;Pimentel, Borin, & Hagelaar, 2006;Payan & Svensson, 2007;Ha, 2010). Hence, trust fosters a sense of security in the reliability and integrity of the other partner (Hunt et al, 2002).…”
Section: Relational Effects: Cooperation and Relationship Learningmentioning
confidence: 99%
“…Different studies of alliances have demonstrated that trust and commitment are two clear antecedents of the generation of cooperative behaviours between partners. First, trust is a major facilitator of cooperation because partners will only take high risks in cooperation when they have confidence in their counterparts (Morgan & Hunt, 1994;Lancastre & Lages, 2006;Pimentel, Borin, & Hagelaar, 2006;Payan & Svensson, 2007;Ha, 2010). Hence, trust fosters a sense of security in the reliability and integrity of the other partner (Hunt et al, 2002).…”
Section: Relational Effects: Cooperation and Relationship Learningmentioning
confidence: 99%
“…Thus, we respond to the challenge of Pimentel et al (2006) and Sila et al (2006) regarding the necessity of additional models and unexplored variables for a better understanding of the long-term approach of the relationships that take place in the SCM field. Our sample considers SMEs in such a way that, looking at Morrissey and Pittaway (2006) and Quayle's (2003) call, we get further through the study of this business context.…”
Section: Discussionmentioning
confidence: 96%
“…Pimentel, Borin, & Hagelaar, 2006;Sila et al, 2006) have recently drawn attention to the need for papers presenting additional models that contribute toward a better understanding of this relational framework, analyzing factors that have not been considered up to now. We have not found any previous papers that consider how the firm's age can affect the long-term orientation of firm -supplier relationships.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…On the other side, normative commitment allows establishing objectives and shared values. Other works, [29] and [30] do not include in their works the commitment factor but they consider trust an essential factor of collaboration. [29] analyze the impact of three factors: trust, ICT, and information network on the joint efforts (planning and conflict resolution).…”
Section: Empirical Models Of Collaborationmentioning
confidence: 99%
“…Other works, [29] and [30] do not include in their works the commitment factor but they consider trust an essential factor of collaboration. [29] analyze the impact of three factors: trust, ICT, and information network on the joint efforts (planning and conflict resolution). In [30] trust is a mediator factor between other factors such as participation, communication, learning capability, and ability to share knowledge to finally obtain inter-organizational knowledge share.…”
Section: Empirical Models Of Collaborationmentioning
confidence: 99%